1996
DOI: 10.1080/00268979600100751
|View full text |Cite
|
Sign up to set email alerts
|

The solvation of sodium ions in water clusters: intermolecular potentials for Na+-H2O and H2O-H2O

Abstract: New model potentials are constructed for Na + H~O and H20-H20, using quantum mechanical calculations of the monomer wavefunctions. One parameter in each model potential is fitted to experimental dimer properties. The resulting Na+-H20 potential is consistent with published thermodynamic and ab initio data, and the H~O-H20 potential reproduces the structure and energy of the water dimer at equilibrium, and the second virial coefficient of steam, within experimental uncertainties. The donor-acceptor interchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…In fact, it has been shown that the hydrophobicity of these cations effectively impedes the irreversible oxidation and surface roughening of Pt(111) electrocatalysts during oxide formation and reduction processes in alkaline media by inhibiting the formation of OH ads /O ads (H 2 O) on the surface . On the other hand, Na + establishes stronger interactions with H 2 O in its solvation shell than TBA + . , Different interactions with H 2 O could alter the state of the OH ads adlayer on Pt(111). Importantly, these results show that at these low concentrations, TBA + does certainly interact with the surface, although this is not visible from the H UPD region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been shown that the hydrophobicity of these cations effectively impedes the irreversible oxidation and surface roughening of Pt(111) electrocatalysts during oxide formation and reduction processes in alkaline media by inhibiting the formation of OH ads /O ads (H 2 O) on the surface . On the other hand, Na + establishes stronger interactions with H 2 O in its solvation shell than TBA + . , Different interactions with H 2 O could alter the state of the OH ads adlayer on Pt(111). Importantly, these results show that at these low concentrations, TBA + does certainly interact with the surface, although this is not visible from the H UPD region.…”
Section: Resultsmentioning
confidence: 99%
“… 38 On the other hand, Na + establishes stronger interactions with H 2 O in its solvation shell than TBA + . 27 , 39 Different interactions with H 2 O could alter the state of the OH ads adlayer on Pt(111). Importantly, these results show that at these low concentrations, TBA + does certainly interact with the surface, although this is not visible from the H UPD region.…”
Section: Resultsmentioning
confidence: 99%